Use of a Spinal Thermal Massage Device for Anti-oxidative Function and Pain Alleviation - Kim, Ka-Eun; Park, Jeong-Sook; Cho, Il-Young; Yoon, Yong-Soon; Park, Soon-Kwon; Nam, Sang-Yun (Frontiers in Public Health, 2020)
Background: Elderly people are vulnerable to a variety of diseases, including chronic pain, which reduces their levels of physical fitness. Thermal massage has been shown to relieve pain and activate antioxidant enzymes. The objective of this study was to determine whether thermal massaging of the spinal column can reduce muscle pain and induce antioxidant function. Methods: This study included participants aged ≥60 years with lower back pain. The participants were assigned to either an experimental group who received spinal column thermal massage and standard rehabilitative treatment or a control group who received standard rehabilitative treatment only. Data from a total of 116 participants (61 and 55 in the control and experimental groups, respectively) were used for analysis. Participants were assessed before treatment and at 4 (POST1) and 8 weeks (POST2) post-treatment, using a pain numeric rating scale (PNRS) and the Roland and Morris Disability Questionnaire (RMDQ), and by measuring the serum levels of superoxide dismutase (SOD), serum glutathione-peroxidase (GPx), and serum catalase (CAT). Results: The extent of pain reduction, as measured by the PNRS, was greater in the experimental group. The RMDQ score in the control group decreased at POST1, but the decrease was not maintained at POST2, whereas the decrease in POST1 in the experimental group continued until POST2. SOD concentrations were significantly higher in the experimental group at POST1 and POST2, and GPx levels were significantly higher in the experimental group at POST2; however, there were no changes in CAT concentrations. Incidentally, there was a significant correlation between antioxidant activity and pain perception in the experimental group. Conclusions: The study findings suggest that spinal column thermal massage reduces pain more effectively, improves self-reported levels of disability, and increases the antioxidant enzyme levels. Thermal massage may, therefore, be useful in the prevention and treatment of diseases associated with oxidation.